Two Thousand Miles on an Automobile : Being a Desultory Narrative of a Trip Through New England, New York, Canada, and the West, By "Chauffeur" - Eddy, Arthur Jerome, 1859-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Two Thousand Miles on an Automobile" by Arthur Jerome Eddy is a travel narrative written in the early 20th century that encapsulates the excitement and challenges of an automobile journey through New England, New York, Canada, and the West. The writer, who refers to himself humorously as "Chauffeur," embarks on this adventure accompanied by a character known as the Professor. The narrative not only chronicles their travels but also delves into the intricacies of operating an automobile during a time of technological innovation and social change. The opening of the book introduces the reader to the author's reflections on the automobile itself, illustrating the capricious nature of gasoline engines and the necessary skills required to handle them. It emphasizes a variety of human interactions that unfold during their travels, from charming exchanges with curious bystanders to humorous encounters with the local populace, particularly with children and farm workers. As they prepare to start their journey, the author sets the stage for an exploration of both the landscapes they traverse and the sociocultural dynamics of late 19th-century North America. The tone is informal and reflective, infused with humor, presenting a rich backdrop for the unique experiences that lie ahead. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Holly Ingraham
Keywords: United States -- Description and travel; United States -- Social life and customs -- 1865-1918; Eddy, Arthur Jerome, 1859-1920 -- Travel -- United States; Automobile travel -- United States -- History -- 20th century